Scientometric Analysis of Hiking Tourism and Its Relevance for Wellbeing and Knowledge Management - Acevedo-Duque, Ángel (2022)
Hiking is a sports activity that takes place in the natural environment. From the point of view of well-being, it is an aerobic activity that prevents and improves cardiovascular diseases. According to data provided by the United Nations, within the framework of the International Year of Mountains, mountain tourism represents around 15% to 20% of total world tourism revenue. This approach aims to critically analyze the scientific production on trail tourism (HT) with contributions from authors from around the world from 1991 to 2022, in order to respond to the connection between this research, knowledge management and the sustainable development of the industry. Key knowledge contributions are examined using a scientometric approach as a method (spatial, production, impact, and relational) based on registry data stored in the Web of Science (JCR and ESCI). Regarding the results, there has been an increase in scientific production in the last decade, which is manifested in the quality of the publications.